Susceptibility/resistance of Anticarsia gemmatalis larvae to its nucleopolyhedrovirus (AgMNPV): Structural study of the peritrophic membrane - Levy, Sheila M.; Falleiros, Ângela M. F.; Moscardi, Flávio; Gregório, Elisa A. (Elsevier, 2007)
This investigation compares the peritrophic membrane (PM) morphology along the midgut of susceptible (SL) and resistant (RL) Anticarsia gemmatalis larvae to the AgMNPV. The PM increased the thickness from the anterior to the posterior midgut region in both insects strain; however, the intensity of FITC-WGA reaction of the PM in the RL were greater than in SL. The PM in RL was ultrastructurally constituted by several layers of fibrous/vesicular materials in comparison with the few ones in SL. Our results showed that the structure of PM in the RL could be one of the resistance barriers to AgMNPV. © 2007.
Keywords: Chitin; Lepidoptera; Midgut; Nuclear polyhedrosis virus; Peritrophic membrane; Resistance; Velvet bean caterpillar; animal; animal disease; cell membrane; comparative study; cytology; digestive system; disease predisposition; innate immunity; larva; pathogenicity; Polyhedrosis virus; ultrastructure; virology; Animals; Cell Membrane; Digestive System; Disease Susceptibility; Immunity, Natural; Larva; Nucleopolyhedrovirus; Anticarsia gemmatalis; Anticarsia gemmatalis nucleopolyhedrovirus; Hexapoda; Mucuna